2013
DOI: 10.1016/j.jcin.2012.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic Success and Procedural Complications in Patients Undergoing Percutaneous Coronary Chronic Total Occlusion Interventions

Abstract: CTO PCI carries low risk for procedural complications despite high success rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
199
2
14

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 340 publications
(229 citation statements)
references
References 29 publications
14
199
2
14
Order By: Relevance
“…This finding contrasts with previous clinical studies, which reported malignant diseases as the most common cause of pericardial tamponade, reaching 30-60% of cases [6][7][8][9][10][11]. This shift in tamponade etiology is apparently due to the increase in recent years in the overall number and in the complexity of percutaneous intra-cardiac procedures, as well as the introduction of interventional techniques such as trans-catheter valve replacement and catheter ablation for atrial fibrillation, all reported to be possibly complicated by cardiac tamponade [12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…This finding contrasts with previous clinical studies, which reported malignant diseases as the most common cause of pericardial tamponade, reaching 30-60% of cases [6][7][8][9][10][11]. This shift in tamponade etiology is apparently due to the increase in recent years in the overall number and in the complexity of percutaneous intra-cardiac procedures, as well as the introduction of interventional techniques such as trans-catheter valve replacement and catheter ablation for atrial fibrillation, all reported to be possibly complicated by cardiac tamponade [12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…Since the pooling of blood was observed at the distal portion of the vessel, we conjecture that a floppy guidewire penetrated the intima of the vessel and advanced into the sub-epicardial space. A meta-analysis of the risk of complications during CTO coronary intervention demonstrated that coronary perforation is not a rare complication and has an incidence rate of 2.9%, but that cardiac tamponade and death are rare with incidence rates of 0.3% and 0.2%, respectively [8]. Cardiac tamponade is generally caused by pooling of blood in the pericardial space between the epicardium and pericardium.…”
Section: Discussionmentioning
confidence: 99%
“…A meta‐analysis of 65 studies published between 2000 and 2011 reported 77% angiographic success and 3.1% risk for MACE 24. In recent years, several large multicenter registries have reported higher success (≈85%–90%) with acceptable complication rates in CTO PCI at various experienced centers and with operators from all around the world, although less optimal results have been reported from all‐comer PCI registries (Table 2).…”
Section: Success Of Cto Pcimentioning
confidence: 99%